Atomically dispersed hybrid nickel-iridium sites for photoelectrocatalysis - Chunhua Cui (Nature Portfolio, 2017)
Atomically disperse catalysts can offer promising activity due to the high exposure of active sites. Here, iridium complexes in solution undergo a binding equilibrium with a nickel oxide surface resulting in atomically disperse iridium and high turnover frequencies for oxygen evolution.